The critical value of György Márkus's philosophical anthropology: Rereading Marxism and Anthropology: The Concept of 'Human Essence' in the Philosophy of Marx. (February 2015) - Jaffe, Aaron
This article critically re-reads György Márkus's seminal Marxism and Anthropology in light of its recent reissue with an introduction by Hans Joas and Axel Honneth. Joas and Honneth problematically identify the normative source of Márkus's position as an a-historical and extra-natural account of the human. In fact, when the human essence is thought as natural while also historical, developing new powers and needs through changing strategies of socially organized work, Marx's materialist conception of history can be used to generate a critique of social organizations, relations, and structures that constrain rather than promote such development. Such constraint on developing powers can be read as 'alienation' from the human essence. Márkus's work develops this reading of Marx in a textually sensitive way, but his analysis of alienation in the Economic and Philosophical Manuscripts of 1844 focuses on the individual when such analysis could in fact be profitably extended to apply to groups and the species as whole.